Evaluation of smear microscopy and geneXpert for the rapid diagnosis of pulmonary and extrapulmonary tuberculosis in a tertiary care hospital in North India: a descriptive prospective study - Zahoor, Danish; Farhana, Anjum; Kanth, Farhath; Manzoor, Munazah (International Journal of Research in Medical Sciences, 2018)
Background: Tuberculosis is a global health problem associated with high morbidity and mortality. Rapid diagnosis of tuberculosis is essential for early disease management. Conventional methods like microscopy and culture are associated with low sensitivity and longer time to positivity respectively. The GeneXpert is an integrated device for the rapid detection of Mycobacterium tuberculosis and its sensitivity to rifampicin. We evaluated the performance of gene expert MTB/ RIF assay for the diagnosis of pulmonary and extrapulmonary tuberculosis. Methods: A prospective cross sectional study was carried out in the Department of Microbiology. Samples were subjected to smear microscopy by ZN staining, culture on solid (LJ) and liquid media (BacT Alert) and GeneXpert assay. Results: 122 pulmonary samples and 153 extrapulmonary samples collected from 275 patients were included in the study. Out of these, 48 samples were positive by both culture and Xpert assay and 2 samples were culture positive only. Out of 225 culture negative samples, 3 were positive by GeneXpert. The sensitivity for GeneXpert was much higher compared to smear micrscopy (96 Vs 46% respectively). The Xpert assay also detected 3 rifampcin resistant cases. Conclusions: The test appeared to be as sensitive as culture for the detection of tuberculosis in smear positive, smear negative and extrapulmonary tuberculosis. We recommend the use of GeneXpert assay for the early detection of tuberculosis. We conclude that the test is simple and routine staff can perform the test with minimal training.